Early Results of Eastern Indonesia P-wave Tomography Study Using Regional Events. Issue 1 (October 2021) - Sulaiman, M I; Subakti, P A; Haolia,; Fatimah, D Y; Madrinovella, I; Abdullah, A; Zaky, D A; Oka, A S B; Lubis, M H M; Suhardja, S K; Priyono, A; Widiyantoro, S; et al.
Abstract: The tectonic system of Eastern Indonesia is controlled by several major and minor plates, such as Indo-Australian, Australian plate, and Pacific plates. This area is known for its complexity, and high seismic activity. This study tries to image the complex structures beneath this region by employing regional events data and seismic tomography methods. We used five years of regional events catalog provided by the Indonesian Agency of Meteorology, Climatology, and Geophysics. We have sorted 7336 events recorded between 120° – 136° longitude and 0° – 13°(-) latitude consisting of 46446 P and 15467 S wave arrival data. Relocated hypocenter map shows a better constrain location on seismicity along outer Bandar Arc. A dipping pattern of seismicity is seen that is going deeper to the Banda Sea. The seismicity map also images a steep angle pattern of seismicity that could be related to the subduction slab roll-back model at North of Wetar island. Interestingly, we spotted a seismicity gap in West Seram that could be linked with slab tear zone. The checker-board test suggests a proper resolution is still reliable to a depth of 200 km with a less interpretable model at a depth of 300 km. P-wave tomographic models image the high velocity dipping down going slab. The Banda slab is seen to subduct from south Timor Island to the north, from east Tanimbar and Aru Island to west part, and from north Seram Island to south. We observed the down-going slab meet from all directions at about 300 km beneath the Banda sea. P wave tomogram also shows the Timor Island slab has a steeper dip that agrees with the seismicity pattern. Near the Seram island, we identify a low-velocity anomaly zone infiltrate the Banda slab beneath the shallow part of West Seram, which was previously interpreted as slab tear zone. This study also noticed a higher velocity tomogram model at North of Wetar island that might indicate a back-arc thrust. Lastly, a low-velocity band is also exposed at a shallow depth close to the volcano chain along that Banda volcanic arc.